The Challenges of Dyad Practice in Simulation Training of Basic Open Surgical Skills—A Mixed-Method Study. Issue 1 (February 2022) - Zetner, Diana B.; Konge, Lars; Fabrin, Anja; Christensen, John B.; Thinggaard, Ebbe
Abstract : Introduction: Simulation training at home improves access to training, but motivation can be difficult to maintain. Dyad training could keep trainees motivated. This study aimed to examine the effect of self-regulated training of basic surgical skills in pairs versus individually. Methods: One hundred one medical doctors were included in this prospective, mixed-method, simulation-based study. Participants were randomized to train individually or in pairs during a 6-week course in open surgical skills, consisting of didactic instructions and self-directed training at home. Trainees kept a training log and filled in a questionnaire. Skills were tested before and after the course. Tests were rated by an expert using the Objective Structured Assessment of Technical Skills Global Rating Scale. Results: Ninety-seven doctors completed the study. We found no differences in test score between dyad and individual trainees. Dyad trainees compared with individual trainees improved by 7.23 points (intercept estimate) versus 6.94 points, respectively ( P = 0.881). Dyad trainees trained less frequently [7.3 times (intercept estimate) vs. 12.1 times, P < 0.001, but for longer intervals compared with individual trainees (68 minutes vs. 38 minutes)]. Dyad trainees reported benefits such as having a sparring partner, receiving feedback, corrections, increased motivation, having fun, and more structured training sessions. However, the coordination of training sessions was difficult. Conclusions: No differences were found between dyad trainees and individual trainees in improvement of surgical skills. Off-site dyad training led to fewer, but longer training sessions, which may have negatively impacted the effectiveness of training. Dyad trainees perceived dyad training beneficial. Abstract : Supplemental digital content is available in the text.